Human papillomavirus vaccine uptake and associated factors among adolescent girls in Bona district, Sidama regional state, Ethiopia: a community-based study design - Tiruye, Getahun; Sodo, Aster; Tura, Abera Kenay; Dirar, Anteneh; Debella, Adera; Shiferaw, Kasiye (Frontiers in Public Health, 2025)
IntroductionIn developing nations, adult women’s cancer deaths are mostly caused by cervical cancer. Vaccination against the human papillomavirus (HPV) is one of the cost-effective global strategies for cervical cancer prevention, though vaccine uptake remains low in low-resource settings like Ethiopia. Despite the vaccine’s proven effectiveness in tackling cervical-related deaths, there is a dearth of evidence in Ethiopia, particularly in the study region, regarding the HPV vaccine uptake and its influencing factors.ObjectiveThis study aimed to determine HPV vaccination uptake and its associated factors among adolescent girls aged 14–19 years in the Bona district of Sidama regional State of Ethiopia.MethodsA community-based cross-sectional study was conducted in the Bona district, Sidama region, Ethiopia, from June 1, 2024, to July 29, 2024. A systematic random sampling method was employed to recruit 833 study participants. Data were collected using a pretested, structured interviewer-administered questionnaire. The collected data were entered into Epi Data version 4.6 and exported to SPSS version 25 software for final analysis. Binary logistic regression models were used to identify factors associated with HPV vaccine uptake. Variables with a p-value <0.05 in the multivariable logistic regression were declared statistically significant predictors of HPV uptake.ResultsIn this study, the overall prevalence of HPV vaccination uptake was 49.58% [(95% CI: 46.18–52.98)]. Urban residence [AOR = 2.84 (95% CI: 1.87–4.31)], Educational status with college and above [AOR = 1.79 (95% CI 1.23–3.67)], Overall knowledge about HPV infection vaccine and cervical cancer [AOR = 2.53 (1.82–3.51)] and positive attitude towards vaccination [AOR = 2.12 (95% CI: 1.53–2.94)] were significantly associated with HPV vaccine uptake.ConclusionAlmost one in two girls in the district took the HPV vaccine. The study implies that empowering women through education, promoting health awareness about HPV, cervical cancer, and the HPV vaccine, and implementing targeted interventions for rural populations are essential means to increase HPV vaccine uptake.